Structures of Violence and the Denigration of Law in Christian Thought - Meyer, Barbara U. (Studies in Christian-Jewish Relations, 2018)
This article examines three major patterns of violence in Christian theological thought traditions: supersessionism (the idea that Christianity replaced Judaism), realized eschatology (the presentation of a promised future of reconciliation as basically already present in the world today), and inclusivism (the Christian impulse to integrate others as a universalist aim). Previous scholars have examined these patterns separately, but they have not previously been discussed in a comprehensive effort to analyze Christian thinking habits of degrading others, in particular Judaism. The author's inquiry into structures of thought suggests methodologically that interreligious violence is a highly complex phenomenon that can actually be reduced or increased. Indeed, much progress has been made in the last third of the twentieth century by mainstream churches to renounce supersessionism. But while the discourse with regard to realized eschatology and inclusivism still needs to be developed, one of the key findings here is that all three patterns entail a denigration of law, which in itself still remains at play in Christianity’s relation to Judaism but also in its relation to Islam.